Radiology blues: Comparing occupational blue-light exposure to recommended safety standards. - Wentzel, Mari; Janse van Rensburg, Jacques; Terblans, Jacobus J. (South African Journal of Radiology, 2023)
Background: The blue-light hazard is a well-documented entity addressing the detrimental health effects of high-energy visible light photons in the range of 305 nm -- 450 nm. Radiologists spend long hours in front of multiple light-emitting diode (LED)--based diagnostic monitors emitting blue light, predisposing them to potentially higher blue-light dosages than other health professionals. Objectives: The authors aimed to quantify the blue light that radiology registrars are exposed to in daily viewing of diagnostic monitors and compared this with international occupational safety standards. Method: A limited cross-sectional observational study was conducted. Four radiology registrars at two academic hospitals in Bloemfontein from 01 October 2021 to 30 November 2021 participated. Diagnostic monitor viewing times on a standard workday were determined. Different image modalities obtained from 01 June 2019 to 30 November 2019 were assessed, and blue-light radiance was determined using a spectroscope and image analysis software. Blue-light radiance values were compared with international safety standards. Results: Radiology registrars spent on average 380 min in front of a diagnostic display unit daily. Blue-light radiance from diagnostic monitors was elevated in higher-intensity images such as chest radiographs and lower for darker images like MRI brain studies. The total bluelight radiance from diagnostic display units was more than 10 000 times below the recommended threshold value for blue-light exposure. Conclusion: Blue-light radiance from diagnostic displays measured well below the recommended values for occupational safety. Hence, blue-light exposure from diagnostic monitors does not significantly add to the occupational health burden of radiologists. Contribution: Despite spending long hours in front of diagnostic monitors, radiologists' exposure to effective blue-light radiance from monitors was far below hazardous values. This suggests that blue-light exposure from diagnostic monitors does not increase the occupational health burden of radiologists.